พฤติกรรมการไหลของแก๊สและของแข็งในฟลูอิไดซ์เบดแบบหมุนเวียนที่มีลูปซีล - จารุวรรณ บัติปัน (จุฬาลงกรณ์มหาวิทยาลัย, 2004)
In this research, the effects of aeration rate at recycle chamber, supply chamber, vertical aeration section position and the effect of the ratio of sand and biomass were studied by measuring the solid circulation rate. Sand which used in this work has density 2588 kg/sq.m. particle size distribution between 425 and 1180 micrometre, average particle size 658 micrometre. Biomass are used in this study rice husk, corncob and saw dust with particle size 658, 1770 and 699 micrometre, and density 1500, 1162 and 1451 kg/sq.m., respectively. From this study, aeration rate at recycle chamber is necessary for low density solid recycle rate through loop seal because it causes high pressure inside loop seal which is higher than riser. Aeration rate at supply chamber is the main factor that extends solid volume and reduce particle-particle friction which causes easier horizontal flow into fluidized section of loop seal. When considering aeration rate at vertical aeration, the higher aeration rate, the higher solid recycle rate. For the effect of sand and biomass ratio, when ratio of sand in the mixture increased, the solid recycle rate also increased. Furthermore, solid recycle rate with low density has no effect on pressure drop across loop seal